2018
DOI: 10.1111/rda.13174
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ectopic ovotestis in a dog with XX ovotesticular, SRY‐negative, disorder of sexual development

Abstract: A 1-year-old, previously spayed phenotypic female Poodle/Soft-coated Wheaten Terrier (Whoodle) cross was presented for a suspected ovarian remnant. Serum luteinizing hormone (LH) concentration was below the detection limit (<1 ng/ml Witness LH), and serum progesterone concentration was elevated in the chemiluminescence immunoassay (CLIA; 20 ng/ml), consistent with dioestrus and presence of ovarian tissue. Transabdominal ultrasound revealed a retroperitoneal soft tissue structure suspected to be a gonad. On exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Also, these small patches of ovarian tissue are limited to some areas of the gonadal cortex, for which multiple non-continuous sections of the gonad are needed to establish a sound histological diagnosis of ovotestis. In some cases, the existence of antral follicles or corpora lutea have been described [22], as well as the existence of ovarian cycles [8,23]. However, according to available reports, most XX;SRY-negative dogs never experienced estrus [9,25].…”
mentioning
confidence: 99%
“…Also, these small patches of ovarian tissue are limited to some areas of the gonadal cortex, for which multiple non-continuous sections of the gonad are needed to establish a sound histological diagnosis of ovotestis. In some cases, the existence of antral follicles or corpora lutea have been described [22], as well as the existence of ovarian cycles [8,23]. However, according to available reports, most XX;SRY-negative dogs never experienced estrus [9,25].…”
mentioning
confidence: 99%
“…It can also be the result of dropping a tissue fragment into the surgical site or failing to identify and remove ectopic ovarian tissue. [4][5][6] Studies on surgical complications of postOHE reported that 17 -43% of the referral cases, presented for postoperative complications after ovariohysterectomy, were for ORS. 7,8 Animal's age, breed, body condition, whether the surgical procedure was elective or emergent, and the experience of the surgeon were not associated with a higher likelihood of ORS.…”
Section: Introductionmentioning
confidence: 99%